Improvement of cerebral oxygenation during laparoscopy using intermittent sequential compression of legs - Kuzmanovska B.; Jankulovski, Nikola; Isjanovska, Rozalinda; Kartalov A.; Stefanovski, I (Macedonian Academy of Sciences and Arts, 2011)
The creation of CO₂ pneumoperitoneum during laparoscopy causes a series of adverse effects. Impairment of brain oxygen saturation during laparoscopy is a result of increased intra-abdominal pressure, absorbed CO₂ and increased intracranial pressure. The aim of this study is to investigate the possible effects of pneumatic inter-mittent sequential compression (ISC) of legs on oxygenation of the brain during laparoscopy. 100 patients, ASA groups 1 and 2, subjected to elective laparoscopic cholecystectomy, were included in this study. The patients were divided into two groups consisting of 50 patients each, group I, control group, and group II, where ISC was applied. Oxygen saturation of the mixed venous blood from the internal jugular vein (SjvO₂) is an indirect assessment of cerebral oxygen use (oxygenation of the brain). Blood samples were obtained from the bulb of the right jugular vein, as the dominant side for venous drainage from the brain. Informed consent was obtained from each patient. Blood samples of 2 ml were obtained several times during the operation; the first sample immediately after anesthesia induction in order to establish the baseline values of SjvO₂, the second sample immediately after the creation of the pneumoperitoneum, and then every 15 minutes respectively until the end of the pneumoperitoneum. The last sample was obtained before the extubation of the patients. The ISC in group II was terminated after obtaining the last blood sample. Results showed that the average values of oxygen saturation of the mixed venous blood from the internal jugular vein--SjvO₂ levels were higher in group II where ISC was applied (82.3%→86.4%→85.3%→80.2%→82.8%→80.4%), compared to group I, without ISC (85.5%→77.8%→80.6%→83.8%→84.8%), statistically significant in the second and third measurement for p<0.05 for the second and the third measurement, i.e. after the creation of pneumoperitoneum, when the decreease in the brain oxygenation is most dramatic in the group without ISC. In conclusion, application of intermittent sequential compression of the legs is a simple and safe technique for preserving the brain oxygenation during laparoscopy by restoring the blood return from the legs.